The Effect of Giving Cinnamon Decoction Water on The Healing of Perineal Wounds of Postpartum Women at Sri Wahyuni’s PMB and Erlia Saraswati’s PMB - Nely; Harumi, Ani Media; Sukesi; Jeniawaty, Sherly (Jurnal Ilmiah Kesehatan, 2024)
The puerperium is a sensitive time for mothers because they must care for themselves while recovering after giving birth and caring for their babies. So, a good and effective postpartum healing process can help the mother get through the puerperium. Perineal infection is a common infection in mothers after giving birth. Some literature shows that cinnamon has ingredients that can heal wounds. This study aims to see how the influence of cinnamon cooking water on the healing of perineal wounds in postpartum women. This quantitative study used a quasi-experimental design and a nonequivalent control group design approach. The population in this study were postpartum women who gave birth in March and April 2023, respectively. Using a purposive sampling approach, 60 respondents were selected and were divided into two groups. Observation sheets and checklists were used to collect data. Wilcoxon Signed Rank Test, and Mann Whitney U Test was used to analyze the data. The results showed that the average perineal wound healing in the control group was 1.60, while the average in the intervention group was 1.87. The Wilcoxon Sign Ranked Test results obtained a p-value (0.000), namely <0.05, which means there was a difference in wound healing before and after being given treatment for each group. Then, the results of the Mann-Whitney U Test obtained a p-value (0.021) <0.05, meaning there was a difference in wound healing between the treatment and control groups. So, the conclusion that can be made in this study is that giving cinnamon-boiled water affects the healing of perineal wounds in postpartum mothers.